Can the phenomenon of humour serve as an interpretive key to understand the idea of laughter in the Old Testament? - Hennie A.J. Kruger (In die Skriflig, 2014)
In the past humour was frowned upon by some, but more recently it has become part of innocuous communication between members of society. Against this background, authors also claim that humour functions in the Bible. Very few, if any, are convinced that the opposite might be true. Numerous attempts have been made to determine the meaning of, and develop definitions and theories pertaining to the concept of humour. However, until now no consensus has been reached regarding these concepts. The physiological and psychological meaning of the phenomenon is noted, but the relationship between humour and literary types has attracted more attention. Determining the time of the origin of the concept may indicate a difference in meaning between a contemporary Western and ancient Near Eastern or Middle Eastern (and Israelite) understanding of laughter, humour and mockery, respectively.